Thermoelectric and mechanical properties of bismuth-doped lead telluride - Rogacheva, E. I.; Liubchenko, S. G. (Інститут термоелектрики НАН України, 2005)
The effect of elementary introduced Bi upon thermoelectric properties and microhardness of PbTe is investigated. Non-monotonous behaviour of PbTe properties dependence on bismuth content isestablished. Intricate behaviour of the dependences is associated with the modification of Bi dissolution pattern observed under composition variations as well as percolation effects and selfarrangement processes in the impurity subsystem of the crystal. Concentrations of Bi corresponding to maximum values of thermoelectric power are determined.